(untitled) (Research, Society and Development, 2022)
Basic sanitation is considered an extremely important service for the healthy quality of life of every citizen. Thus, the objective of this study was to carry out a retrospective study, from 2016 to 2020, of basic sanitation in the city of Belém, capital of the state of Pará. In methodological terms, the research is a bibliographic and documentary review, if based on scientific articles and documents of the Companhia de Saneamento do Pará. In addition, it has a qualitative and quantitative character, as it analyzes basic sanitation issues in Belém in the years 2016 to 2020. Data collection was carried out through documents provided by the Companhia de Sanitation of Pará, while data treatment was carried out using descriptive statistics. The results showed good efficiency in terms of water service, with 98.74% coverage of this service, despite the service provision rates not reaching 100%. The sewage service proved to be deficient, as it did not treat more than 50% of the collected sewage. Over the five years studied, the water service showed a significant improvement, while the sewage service required a greater evolution to reach satisfactory rates.